A moment of truth : the life of Zola - McLeave, Hugh (Boson Books, 2001)
A Moment of Truth is a biographical novel of the life and times of Zola. It is also a cultural fresco of late nineteenth-century France. A Moment of Truth tells of Zola's early struggle against poverty and incomprehension; his blood-brother friendship with Paul Cézanne; his backing of the scorned Impressionists; his monumental creation of twenty Rougon-Macquart novels depicting and dissecting the French Second Empire in raw and often lurid prose. Finally, this book details Zola's courageous combat against the whole French establishment to win justice for an obscure Jewish captain, Alfred Dreyf.